Will exhaled nitric oxide monitoring become routine in managing asthma? - Pavord, I; Martin, N (2009)
In this editorial, we outline the rationale for a new approach to the assessment of airway disease based on measurement of airway inflammation using noninvasive markers (inflammometry). Our focus is on measurement of exhaled nitric oxide (FE(NO)), as this technique is simple and affordable, and is applicable in a wide variety of clinical settings. Studies have shown that raised FE(NO) is a useful marker of corticosteroid-responsive airway disease; low FE(NO) may identify patients who can safely reduce or withdraw corticosteroids. However, the optimum use of FE(NO) in clinical practice remains to be established.